Syneresis and sensory acceptability of desserts based on whey proteins concentrates - Celeghin, Adelina Guadalupe (2016)
Synereis and sensory acceptability of dairy desserts based on whey proteins concentrate were investigated. Samples were prepared with whey protein concentrate, modified corn starch, cocoa and sucrose or sucralose. For sensory acceptability evaluation sam´ples were compared to a semisolid low in calories commercial dessert based on skim milk. Syneresis was lower than 5% in all the samples studied. This is a successful outcome ecause this is a visual sensory attribute that strongly determines the acceptability of this type of products. Energy values of the samples were similar and minor than the commercial dessert. Samples were qualified mainly by positive degrees of overall liking, though with qualifications lower than those of the commercial dessert. The acceptability of the samples may be improved chnging the concentrations of cocoa, sweeteners and flavoring agent.